Earnings Management in Property Companies Seen from Financial and Control Factors - Sadzili, Rohan As; Suhartini, Dwi (Universitas Kadiri, 2025)
This study analyzed financial distress, cash holdings, profitability, and internal control’s moderating role on earnings management in Indonesian property/real estate firms (2019–2023). Utilizing secondary data from 21 IDX-listed companies, variables were measured via Debt Service Coverage Ratio (financial distress), cash-to-assets ratio (cash holdings), Return on Assets (profitability), Modified Jones Model (earnings management), and an aggregate loss dummy (internal control). Moderated regression analysis (SPSS 28.0) showed: (1) Financial distress and cash holdings negatively impacted earnings management, while profitability increased it; (2) Internal control moderated only financial distress, with no effect on cash holdings or profitability. Financial distress incentivizes earnings manipulation, whereas strong liquidity and profitability deter such practices. Internal control mitigates distress-related risks but lacks efficacy in liquidity/performance contexts. These findings highlight the necessity of robust governance and transparent reporting, especially for financially distressed firms, to reduce opportunistic accounting. Regulators should prioritize oversight mechanisms targeting financial distress, while acknowledging liquidity and profitability as natural safeguards. The study advances understanding of internal control’s conditional role, offering actionable insights for policymakers and corporate leaders in high-risk sectors. Future research should explore sector-specific external factors (e.g., market volatility) to refine governance frameworks.